Equation 1: y = -2x + 1
Equation 2: y = 2x - 3
Since both equations already have y isolated, we are able to simply set the right side of both equations equal to each other. Since we know that the value of y must be the same, we can do this.
-2x + 1 = 2x - 3
1 = 4x - 3
4 = 4x
x = 1
Then, we need to plug our value of x back into either of the original two equations and solve for y. I will be plugging x back into equation 2 above.
y = 2x - 3
y = 2(1) - 3
y = 2 - 3
y = -1
Hope this helps!! :)
Answer:
A
Step-by-step explanation:
You are right
Answer:
50 gluten-free cupcakes and 100 regular cupcakes.
Step-by-step explanation:
Let's define the variables:
R = number of regular cupcakes sold
G = number of gluten-free cupcakes sold
The total amount of money raised then is:
M = R*$2.00 + G*$3.00
We also know that:
The number of regular cupcakes sold was 2 times the number of gluten-free cupcakes sold.
then:
R = 2*G
And we also know that the amount of money raised is $350
Then we have the equations:
R = 2*G
R*$2.00 + G*$3.00 = $350
We can replace the first equation into the second one, so we have only one variable:
(2*G)*$2.00 + G*$3.00 = $350
Now we can solve this for G.
G*$4.00 + G*$3.00 = $350
G*$7.00 = $350
G = $350/$7.00 = 50
G = 50
50 gluten-free cupcakes where sold.
And using the equation:
R = 2*G = 2*50 = 100
We can conclude that 100 regular cupcakes were sold.
A little tip: you should put the question in next time :)!